2021
DOI: 10.3390/pathogens10081040
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DNA Extraction from Field-Collected Mammalian Whole Blood on Filter Paper for Trypanosoma cruzi (Chagas Disease) Detection

Abstract: Blood filter paper strips are cost-effective materials used to store body fluid specimens under challenging field conditions, extending the reach of zoonotic pathogen surveillance and research. We describe an optimized procedure for the extraction of parasite DNA from whole blood (WB) stored on Type I Advantec Nobuto strips from both experimentally spiked and field-collected specimens from canine and skunks, respectively. When comparing two commercial kits for extraction, Qiagen’s DNeasy Blood & Tissue Kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…For example, Cardona-Ospina et al ( 2019 ) summarized RNA extraction from FTA cards used for detection and characterization of viral RNA pathogens from fieldwork. Commercially available DNA extraction kits can be optimized to provide the most accurate and precise recovery for molecular epidemiological studies as it was shown for Trypanosoma cruzi DNA extracted from canine and skunk DBS (Gulas-Wroblewski et al 2021 ). The issue of the best practice for preparation of samples from FTA cards for the molecular diagnosis under large-scale epidemiological studies was addressed in the work of Ahmed et al ( 2011 ) using African trypanosomes as a model object.…”
Section: Carriers For Dried Samples and Sample Pretreatmentmentioning
confidence: 99%
“…For example, Cardona-Ospina et al ( 2019 ) summarized RNA extraction from FTA cards used for detection and characterization of viral RNA pathogens from fieldwork. Commercially available DNA extraction kits can be optimized to provide the most accurate and precise recovery for molecular epidemiological studies as it was shown for Trypanosoma cruzi DNA extracted from canine and skunk DBS (Gulas-Wroblewski et al 2021 ). The issue of the best practice for preparation of samples from FTA cards for the molecular diagnosis under large-scale epidemiological studies was addressed in the work of Ahmed et al ( 2011 ) using African trypanosomes as a model object.…”
Section: Carriers For Dried Samples and Sample Pretreatmentmentioning
confidence: 99%
“…We evaluated 2 sample types: blood filter paper and ear punch samples. Filter paper has been validated as a suitable sample type for disease detection (e.g., avian influenza, Chagas disease), 11,14 and allows for sample collection in the field with little training, equipment, and without the need for climate-controlled transport. 6 Samples must be eluted from filter paper before analysis, leading to lower sensitivity in some assays.…”
mentioning
confidence: 99%
“…Hong et al [8] prioritised the development of an accurate and cost-effective diagnostic test, as well as the use of animals as sentinels, as effective tools for the epidemiological surveillance of leishmaniases. Gulas-Wroblewski et al [9] developed cost-effective DNA storage and DNA extraction methods for the molecular detection of Trypanosoma cruzi in field-based investigations. Furthermore, Zheoat et al [10] discovered that 2 ,4 -dimethoxy-6 -hydroxychalcone from a plant extract of Polygonum salicifolium had anti-leishmanial and anti-trypanosomal effects in the absence of toxicity against a human cell line, suggesting its potential use against Leishmania mexicana, Trypanosoma brucei and T. congolense.…”
mentioning
confidence: 99%